Arahan Peningkatan Kenyaman Taman Venus Sebagai Ruang Terbuka Hijau Publik Kota Sangatta: Arahan Peningkatan Kenyaman Taman Venus Sebagai Ruang Terbuka Hijau Publik Kota Sangatta - Arifin, Marella Hikmatyara; Astha, Dwinsani Pratiwi; Mustofa, Umar; Depari, Andi Sahputra (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
A comfortable garden can be realized by paying attention to aspects of circulation, aroma, shape, safety, cleanliness and beauty. The goal to be achieved in this research is to provide directions for increasing the comfort of Venus Park based on visitor perceptions. Comparative descriptive analysis is a method used to formulate directions for increasing park comfort by comparing the results of the analysis with existing literature and policy studies. The output obtained is increasing the comfort of the park in the circulation variable by widening the pedestrian area and arranging the vehicle parking area, the aroma variable by planting shrubs in the area around the rubbish dump, the shape variable by recommending chairs made of anti-corrosion material and the addition of a prayer room, the security variable by adding CCTV at several points and the addition of pedestrian lights, the cleanliness variable by managing rubbish disposal, the beauty variable by redesigning garden lights and garden chairs with the addition of batik carvings and planting shrubs in areas experiencing drought, as well as managing the cleanliness of fish ponds and repairing fountains.